Analisis Media Permainan Ular Tangga untuk Meningkatkan Keaktifan Siswa - Affnyani (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
Many students have not been able to master the learning material. The students do not fully understand the material even though the teacher has explained. Students quickly feel bored with the material taught because of the monotonous learning process, this is what does not give an impression and increase student activeness, so that their learning outcomes are not satisfactory. This is known by researchers when researchers conducted observations at MI Raden Fatah 02 Grobog Wetan, Therefore, researchers have examined using snakes and ladders learning media in an effort to increase student learning activeness in Al-Quran Hadith subjects. And the research objectives in this study are to increase student activeness in learning. The research method used is Classroom Action Research (PTK), which is research intended to provide input on how to take the right action to increase student activeness in learning Al-Quran Hadith. This class action research will be carried out through four stages, namely planning, implementation, observation, and reflection. Then the research subjects in this study were all 6th grade students of MI Raden Fatah 02 consisting of 8 male students and 12 female students. With the application of snakes and ladders learning media, students actively participate in learning activities, students no longer sit still and the results of learning activeness obtained by students in Al-Quran Hadith subjects are in the very good category. This can be proven from the results of observer observations during the research process that students are very active during the learning process. This study concludes that the application of snakes and ladders learning media can increase student learning activeness in the subject of Al-Quran Hadith QS. Al-Qadr.